Principal Managerial Competence in Improving Teacher Performance - Nursyifa Aprilia Dewi; Hanafiah Hanafiah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This research is motivated by the critical role of the principal as an educational leader in cultivating professional and highly competent teachers amidst complex educational challenges, particularly within private early childhood institutions. The purpose of this study is to determine, describe, and deeply analyze how the principal's managerial competence drives the improvement of teacher performance in Early Childhood Education (PAUD). The philosophical foundation of this study is rooted in humanistic educational thinking, while the theoretical framework utilizes George R. Terry’s managerial competence model. This study employs a qualitative approach with a case study design, grounded in a constructivist paradigm. Data collection utilized methodological triangulation through in-depth interviews, participant observation, and documentation analysis. Data were systematically sourced from foundations, committees, principals, teachers, and school archives across two private institutions: TK Al-Hikmah and RA Nuururrohmaan. The findings reveal that the principal's managerial functions—planning, organizing, actuating, and evaluating—have been executed with maximum effort. However, implementation faces systemic constraints, including limited human resources, insufficient structural support, resistance to organizational change, and uneven managerial skill sets. Concurrently, teachers face challenges such as role ambiguity regarding delegated tasks and a lack of institutionalized workshops for continuous professional development. Despite these barriers, the principals have initiated strategic solutions, including optimizing infrastructure and actively involving foundations, school committees, parents, and the broader community in the educational process. The study concludes that the effective, collaborative, and systematic managerial competence of the principal exerts a highly significant influence on the continuous improvement of teacher performance.